ENGLISH AS A FOREIGN LANGUAGE (EFL) STUDENTS’ PROBLEMS IN LISTENING ENGLISH STORY VIA YOUTUBE - Asma Ulhusnah; Ahmad Talib; Samtidar Samtidar (Universitas Negeri Makassar, 2022)
The aims of this research are to find out the students’ most frequent problems in listening English story via YouTube and the students’ ways to solve their problems. This research applied mixed method, which used both quantitative and qualitative approach. To achieve the purpose of the study the data in this research were collected through online questionnaire and online interview. The respondents of this study were 30 students of English Education 2018, State University of Makassar who participated in online questionnaire and there are 15 students who participated in online interview. The result of data analysis found that (1) there are five most frequent problems students faced when listening English story: lack of vocabulary with 3.93 mean value and percentage of 83.3%, noisy atmosphere with 3.82 mean value and percentage of 65%, lack of knowledge about the topic with 3.80 mean value and percentage of 58%, speaker speaks a bit fast with 3.65 mean value and percentage of 67%, lack of grammar with 3.63 mean value and percentage of 68.3%, (2) there are two ways in solve their problems in each factor. Those are taking a note and practice listening through audio and video, looking for a comfortable place and try to focus and concentrate, looking for the information of the topic and try to understand the topic, repeat the audio or video and use the subtitle feature, learning a lot and reading a book.